Preparation method for electrochemical in-situ synthesis of Cu / DNBT film
Through the electrochemical in-situ synthesis of Cu/DNBT films, the problem of difficult to achieve miniaturization and intelligence of ignition devices in pyrotechnical products is solved, and high integration, ultra-miniature and excellent ignition performance are achieved.
Patent Information
- Application Number
- CN202411636283.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-15
- Publication Date
- 2025-02-21
- Estimated Expiration
- 2044-11-15
AI Technical Summary
It is difficult to achieve miniaturization, lightweight, integrated and intelligentization of existing ignition devices, which limits the development of civil explosive systems and other equipment.
The preparation method of electrochemical in-situ synthesis of Cu/DNBT films is ultrasonic cleaned by dilute sulfuric acid and anhydrous ethanol to form a nanoscale Cu(OH)2 film, and DNBT is deposited on its surface by coordination reaction to form a Cu/DNBT film.
It realizes high integration, ultra-minizability and good ignition performance of Cu/DNBT films, and improves the ignition reaction speed and heat release ability of pyrotechnics.
Smart Images

Figure CN119491281A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of micro-charges of explosive devices, and in particular is a preparation method of a Cu / DNBT thin film by electrochemical in-situ synthesis. Background Art
[0002] An initiator is a functional starting device that provides ignition, explosion or power. Ignition devices are one of the core categories of initiators, and their development restricts and affects the development of civilian explosion systems, etc. With the increasing demand for civilian equipment such as smart airbags in modern technology, miniaturized, lightweight, integrated, and intelligent ignition devices are becoming the research direction of initiator technology. Micro-electromechanical systems are becoming an important means to achieve miniaturization, integration, and intelligence due to their high integration, ultra-miniaturization, and advantages combined with digital logic circuits. Therefore, the application of MEMS technology in the field of initiators provides a technical approach for the development of MEMS initiator chips with excellent performance such as low-energy ignition, high-energy output, miniaturization, and high integration. Summary of the invention
[0003] The purpose of the present invention is to solve the problems existing in the above-mentioned prior art and to provide a method for preparing a Cu / DNBT thin film by electrochemical in-situ synthesis.
[0004] The present invention is achieved through the following technical solutions: A method for preparing a Cu / DNBT thin film by electrochemical in-situ synthesis comprises the following steps: 1) Synthesis of DABT Hydrochloric acid was added to the mixture of oxalic acid and aminoguanidine bicarbonate, and the mixture was stirred at 70° C. for 1 hour. Finally, the precipitate was collected by filtration to obtain a colorless solid.
[0005] The colorless solid was dissolved in water, alkalized to pH 14 with sodium hydroxide, then heated to reflux for 1 hour, then acidified to pH 4 with acetic acid, and finally the precipitate was collected by filtration and washed with water to obtain the DABT (i.e., 5,5′-diamino-3,3′-bis(1,2,4-triazole)).
[0006] 2) Synthesis of DNBT A 20% sulfuric acid solution of DABT is dropped into a 40°C sodium nitrite aqueous solution and stirred at 50°C for 1 hour; after cooling to room temperature, the obtained mixture is acidified with sulfuric acid until no generation of nitrogen dioxide is observed; the precipitate is collected by filtration, and then the precipitate is dissolved in boiling water, the hot solution is filtered and cooled to room temperature to obtain the DNBT (i.e., 5,5′-dinitro-3,3′-bis(1,2,4-triazole)).
[0007] 3) Modification of the Cu substrate surface The copper foil was ultrasonically cleaned with dilute sulfuric acid and anhydrous ethanol to remove oil stains and oxide layers on the surface; it was then cleaned with deionized water to remove residual ethanol on the surface.
[0008] The cleaned Cu foil was vertically immersed in a mixed alkaline solution containing sodium hydroxide and (NH4)2S2O8, then rinsed with deionized water, and finally dried at a constant temperature of 25°C to obtain a Cu foil with a blue nanoscale Cu(OH)2 film coated on the surface.
[0009] 4) Electrochemical in-situ synthesis of Cu / DNBT thin films The Cu foil coated with a blue nano-scale Cu(OH)2 film is immersed in a DNBT aqueous solution, the Cu foil coated with a blue nano-scale Cu(OH)2 film is used as an anode, and a platinum foil is used as an auxiliary electrode. After a coordination reaction, a light green film is obtained on the surface of the Cu foil, which is the Cu / DNBT film. Finally, the copper foil containing the Cu / DNBT film is taken out from the reaction solution, rinsed with deionized water, dried at 25° C. and then stored.
[0010] As a preferred technical solution, in step 1) of the above method, the amount of hydrochloric acid used is 60 mL, the amount of oxalic acid used is 20.0 g, and the amount of aminoguanidine bicarbonate used is 45.4 g.
[0011] As a preferred technical solution, in step 2) of the above method, in the sulfuric acid solution of DABT, the amount of DABT used is 11.9 g, and the amount of 20% sulfuric acid used is 140 mL; in the sodium nitrite aqueous solution, the amount of sodium nitrite used is 98.8 g, and the amount of water used is 40 mL; the concentration of sulfuric acid used for acidification is 20%.
[0012] As a preferred technical solution, in step 3) of the above method, the concentration of dilute sulfuric acid used for ultrasonic cleaning is 20%, and the ultrasonic cleaning time is 5 min; the concentration of sodium hydroxide in the mixed alkaline solution is 1.17 mol·L −1 , the concentration of (NH4)2S2O8 is 0.087 mol·L −1 , the immersion time of Cu foil in the mixed alkaline solution is 10 min.
[0013] As a preferred technical solution, in step 4) of the above method, the concentration of the DNBT aqueous solution is 0.01 mol·L −1 , the dosage is 40 mL; the coordination reaction adopts a constant voltage of 1.5 V and the reaction time is 20 min.
[0014] Furthermore, in order to improve the energy of the Cu / DNBT film prepared by the above method, the present invention also provides a method for preparing a Cu / DNBT@nano-Al energetic film based on the above Cu / DNBT film, comprising the following steps: 1) Dissolve nitrocellulose (NC) in acetone solution, then add Al powder and disperse it under the action of ultrasound to obtain high-energy aluminum-containing ink.
[0015] 2) Using a spin coating device (spin coating machine) to uniformly coat the high-energy aluminum-containing ink on the surface of the Cu / DNBT film prepared by the method of claim 1; after evaporation of acetone, a dark green film is obtained on the surface of the Cu foil, which is the Cu / DNBT@nano-Al energetic film.
[0016] As a preferred technical solution, in step 1) of the above method, the amount of nitrocellulose used is 0.075 g, the amount of acetone used is 45 mL, the particle size of Al powder is 200 nm, the amount added is 0.425 g, and the ultrasonic dispersion time is 40 min.
[0017] The present invention provides a preparation method of electrochemical in-situ synthesized Cu / DNBT thin film. The preparation method of the present invention is scientifically and rationally designed, simple and convenient to operate, short in preparation time, and good in safety. In the method of electrochemical in-situ synthesis of Cu / DNBT thin film, in order to increase the contact area between the Cu substrate (Cu foil) and the ligand in the electrolyte, the surface of the Cu substrate is modified to cover it with a layer of nanoscale Cu(OH)2 thin film. The nanoscale Cu(OH)2 thin film provides metal ions as an electrochemical anode. Through the coordination reaction of DNBT and Cu(OH)2 thin film, the Cu / DNBT thin film is finally synthesized on the copper foil; although the copper substrate is not the most commonly used copper substrate for MEMS, the copper thin film is easily deposited on the wafer and has good adhesion properties. Therefore, the present invention directly uses Cu foil as the substrate to preliminarily verify the compatibility of MEMS; the density velocity, heat of generation and detonation velocity of the DNBT prepared by the method of the present invention are 1.90g·cm −3 、285kJ·mol −1 and 8413ms −1 , high nitrogen content, can produce a large amount of gas after ignition reaction, and produce a large amount of residual gas after combustion, which improves the ignition performance of the film.
[0018] The present invention also provides a method for preparing a Cu / DNBT@nano-Al energetic film. The method is based on the above-mentioned Cu / DNBT film and aims to further increase its heat release after ignition. The method is to coat a layer of nano-scale aluminum film on the Cu / DNBT film by a rotary coating device (spin coating machine) using a drop coating method, so that the Cu / DNBT film finally has more excellent ignition and detonation performance. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the technical solutions in the embodiments of the present invention, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. The drawings herein are used to provide further explanation of the present invention and constitute a part of this application. The schematic embodiments of the present invention and their description are used to explain the present invention and do not constitute an improper limitation on the present invention.
[0020] Figure 1 The SEM image, macroscopic morphology image and EDS spectrum image of the Cu / DNBT film prepared in the embodiment of the present invention are shown.
[0021] Figure 2 The following are PXRD spectra of relevant products in the preparation method of the embodiment of the present invention.
[0022] Figure 3 FT-IR spectra of relevant products in the preparation method of the embodiment of the present invention.
[0023] Figure 4 It is the DTA curve diagram of each relevant product in the preparation method of the embodiment of the present invention.
[0024] Figure 5 Schematic diagram of laser ignition of the Cu / DNBT film and Cu / DNBT@nana-Al energetic film prepared in the examples. DETAILED DESCRIPTION
[0025] The embodiments of the technical solution of the present invention will be described in detail below in conjunction with the accompanying drawings. The following embodiments are only used to more clearly illustrate the technical solution of the present invention, and are therefore only used as examples, and the protection scope of the present invention cannot be limited thereto. It should be noted that, unless otherwise specified, the technical terms or scientific terms used in this application should be the common meanings understood by those skilled in the art to which the present invention belongs. Example 1
[0026] This embodiment provides a method for preparing a Cu / DNBT thin film by electrochemical in-situ synthesis, which specifically includes the following steps: 1) Synthesis of DABT Add hydrochloric acid (60 mL) to a mixture of oxalic acid (20.0 g, 159 mmol) and aminoguanidine bicarbonate (45.4 g, 332 mmol), stir and react at 70 °C for 1 hour, and finally collect the precipitate by filtration to obtain a colorless solid; The colorless solid was dissolved in water (240 mL), alkalized to pH 14 with sodium hydroxide, then heated to reflux for 1 hour, then acidified to pH 4 with acetic acid, and finally the precipitate was collected by filtration and washed with water to obtain the DABT; 2) Synthesis of DNBT A 20% sulfuric acid (140 mL) solution of DABT (11.9 g, 72 mmol) was added dropwise to a 40°C sodium nitrite (98.8 g) aqueous solution (140 mL), and the mixture was stirred at 50°C for 1 hour; after cooling to room temperature, the obtained mixture was acidified with sulfuric acid (20%) until no nitrogen dioxide was observed to be generated; the precipitate was collected by filtration, and then the precipitate was dissolved in boiling water, the hot solution was filtered and cooled to room temperature, and the DNBT was obtained; 3) Modification of the Cu substrate surface The copper foil (20 mm × 15 mm × 0.1 mm, purity 99.9%) was ultrasonically cleaned for 5 min using dilute sulfuric acid (20%) and anhydrous ethanol to remove the oil stains and oxide layer on the surface; it was then cleaned with deionized water to remove the residual ethanol on the surface. The cleaned Cu foil was vertically immersed in a solution containing 1.17 mol·L −1 Sodium hydroxide and 0.087 mol·L −1 The copper foil was placed in a mixed alkaline solution (20 mL) of (NH4)2S2O8 for 10 min, then rinsed with deionized water, and finally dried at 25 °C to obtain a Cu foil with a blue nanoscale Cu(OH)2 film on the surface. 4) Electrochemical in-situ synthesis of Cu / DNBT thin films A Cu foil (20 mm × 15 mm) coated with a blue nanoscale Cu(OH)2 film was immersed in 0.01 mol·L −1 In a DNBT aqueous solution (40 mL), a Cu foil coated with a blue nanoscale Cu(OH)2 film was used as the anode, and a platinum foil (15 mm×15 mm) was used as the auxiliary electrode. After 20 min of coordination reaction (constant potential of 1.5 V), a light green film was obtained on the surface of the Cu foil, which was the Cu / DNBT film. Finally, the copper foil containing the Cu / DNBT film is taken out from the reaction solution, rinsed with deionized water, dried at 25° C. and then stored. Example 2
[0027] This embodiment provides a method for preparing a Cu / DNBT@nano-Al energetic film, which specifically includes the following steps: 1) 0.075 g of nitrocellulose (NC) was dissolved in 45 mL of acetone solution, 0.425 g of Al powder (particle size 200 nm) was added to the mixed solution of nitrocellulose and acetone, and dispersed under ultrasonication for 40 min to obtain a high-energy aluminum-containing ink; 2) Using a spin coating device (spin coating machine), the high-energy aluminum-containing ink is uniformly coated on the surface of the Cu / DNBT film prepared by the method of Example 1; after the acetone evaporates, a dark green film is obtained on the surface of the Cu foil, which is the Cu / DNBT@nano-Al energetic film.
[0028] The following is a further analysis of the relevant products involved in the preparation method of the embodiment of the present invention, and the specific results are as follows: 1) Cu / DNBT film morphology analysis Figure 1 (a)-(c) are SEM images of Cu / DNBT films at low, medium and high magnifications. From the microscopic morphology in the images, it can be clearly seen that the surface of the prepared Cu / DNBT film presents an interlaced lamella structure with an average flake size of 700nm-1400nm. Figure 1 (d) in the figure shows the macroscopic morphology of the prepared Cu / DNBT film. Figure 1 (e) in the figure is the EDS energy spectrum of the prepared Cu / DNBT film. EDS shows that the prepared Cu / DNBT film is mainly composed of Cu, C, N, and O, and the atomic mass ratios are 28.01%, 19.10%, 30.97%, and 21.91%, respectively.
[0029] 2) Analysis of Cu / DNBT film components The Cu / DNBT thin film prepared in Example 1 was analyzed by PXRD to determine its elemental composition. Figure 2 The PXRD spectra of the relevant products in the preparation method of the embodiment are shown in Figure 1, where (a) is the PXRD spectrum of Cu / DNBT powder, (b) is the PXRD spectrum of Cu / DNBT@nano-Al energetic film, (c) is the PXRD spectrum of Cu(OH)2 film, and (d) is the PXRD spectrum of Cu / DNBT film. Figure 2 As shown in (b)-(d) in the figure, the diffraction peaks at 43.3, 50.3 and 74.4 in the Cu / DNBT film correspond to the diffraction peaks of the Cu substrate, and the diffraction peaks at 16.7 and 23.8 are standard Cu(OH)2. Figure 2As shown in (a) and (b), the diffraction peaks of the Cu / DNBT film at 14.3 and 28.6 correspond to the Cu / DNBT powder, confirming that Cu / DNBT was successfully synthesized on the film surface.
[0030] In order to further determine the composition of each related product, Fourier transform infrared (FT-IR) spectroscopy was used to analyze each related product. Figure 3 The FTIR spectra of the relevant products in the preparation method of the embodiment are shown in Figure 1, where (a) is the FT-IR spectrum of the Cu(OH)2 film, (b) is the FT-IR spectrum of the Cu / DNBT film, (c) is the FT-IR spectrum of the Cu / DNBT powder, and (d) is the FT-IR spectrum of the Cu / DNBT@nano-Al energetic film. Figure 3 As shown in (d), there is no infrared absorption peak in the FT-IR spectrum because there is no functional group in the nano-aluminum structure. The FT-IR spectrum of the Cu(OH)2 array has a peak at 3564 cm −1 and 3296cm −1 The peak at is related to the OH bond. Figure 3 As shown in (b), the peak is at 1537cm −1 、1439cm −1 、1365cm −1 、1174cm −1 , and 1099cm −1 Belongs to the triazole ring and NO2 bond. Figure 3 (b) and (d) show the FT-IR spectra of Cu / DNBT film and the FT-IR spectra of Cu / DNBT powder. Figure 1 The results show that the Cu / DNBT thin film was successfully prepared on the Cu substrate.
[0031] 3) Performance analysis of Cu / DNBT film The exothermic characteristics of Cu / DNBT film were analyzed by DTA method. Figure 4 The DTA curves of the relevant products in the process of the preparation method of the embodiment are shown in Figure 1, where (a) is the DTA curve of Cu / DNBT powder, (b) is the DTA curve of Cu / DNBT film, (c) is the DTA curve of Cu / DNBT@nano-Al energetic film coated with aluminum for 3 times, (d) is the DTA curve of Cu / DNBT@nano-Al film coated with aluminum for 4 times, and (e) is the DTA curve of Cu / DNBT@nano-Al film coated with aluminum for 5 times. Figure 4As shown in (a) and (b) in Figure 1, the DTA curve of the Cu / DNBT film is consistent with that of the Cu / DNBT powder, and a significant exothermic peak is observed at 357.5°C, which corresponds to the decomposition of the DNBT ligand. Compared with the initial reaction temperatures of many typical high-energy materials, such as HMX (287°C) and RDX (230°C), the thermal stability of Cu / DNBT is significantly better, indicating that the safety is improved. Figure 4 As shown in (c) in Figure 3, in addition to the obvious exothermic peak near 358.3℃, there is also an obvious exothermic peak at 587.9℃. This is because the copper oxide produced by the Cu / DNBT film reacts with the aluminum-containing ink to release a large amount of heat. In addition, the addition of nano-aluminum also improves the heat release of the energetic film, such as Figure 4 As shown in (c)-(e) in Figure 2, with the increase of the number of aluminum plating times, the heat release of Cu / DNBT@nana-Al energetic film also increases (1592.4 J·g −1 、1691.8J·g −1 and 1823.1 J·g −1 ).
[0032] 4) Laser ignition test Figure 5 High-speed photography images of laser ignition of Cu / DNBT film and Cu / DNBT@nana-Al energetic film, where (a) is the laser ignition of Cu / DNBT film prepared by 20 min and 1.5 V reaction, (b)-(d) are the laser ignition of Cu / DNBT@nano-Al film coated with aluminum 3, 4, and 5 times. Figure 5 A bright flash can be observed in the figure, confirming the successful ignition of the prepared Cu / DNBT film and Cu / DNBT@nano-Al energetic film. The ignition height and duration are 12.5 mm and 200 μs, respectively. In addition, the ignition time and flame height of the Cu / DNBT@nano-Al energetic film increase with the increase of the number of aluminum plating times. As the number of aluminum plating times increases from 3 to 5, the ignition time of the Cu / DNBT@nano-Al energetic film increases from 250 μs to 400 μs, and the flame height increases from 11.2 mm to 13.5 mm. These results show that increasing the amount of aluminum plating on the Cu / DNBT@nano-Al energetic film can improve the ignition time, flame height and flame brightness of the film. The Cu / DNBT@nano-Al energetic film produces solid residues during the ignition process, releases a large amount of heat, and produces a large amount of high-temperature and high-pressure gas. The hot solid particles impact the ignited particles under the push of the high-temperature and high-pressure gas, which improves the ignition performance of the MEMS device.
[0033] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some or all of the technical features may be replaced by equivalents. These modifications or replacements do not deviate the essence of the corresponding technical solutions from the scope of the technical solutions of the embodiments of the present invention, and they should all be included in the scope of the claims and specification of the present invention.
Claims
1. A method for preparing a Cu / DNBT thin film by electrochemical in-situ synthesis, characterized in that: The steps include: 1) Synthesis of DABT Add hydrochloric acid to the mixture of oxalic acid and aminoguanidine bicarbonate, stir and react at 70°C for 1 hour, and finally collect the precipitate by filtration to obtain a colorless solid; The colorless solid is dissolved in water, alkalized to pH 14 with sodium hydroxide, then heated to reflux for 1 hour, then acidified to pH 4 with acetic acid, and finally the precipitate is collected by filtration and washed with water to obtain the DABT; 2) Synthesis of DNBT A 20% sulfuric acid solution of DABT is dripped into a sodium nitrite aqueous solution at 40°C, and stirred at 50°C for 1 hour; after cooling to room temperature, the obtained mixture is acidified with sulfuric acid until no nitrogen dioxide is observed to be generated; the precipitate is collected by filtration, and then the precipitate is dissolved in boiling water, the hot solution is filtered and cooled to room temperature, thereby obtaining the DNBT; 3) Modification of the Cu substrate surface The copper foil was ultrasonically cleaned with dilute sulfuric acid and anhydrous ethanol to remove the oil stains and oxide layer on the surface; then it was cleaned with deionized water to remove the residual ethanol on the surface; The cleaned Cu foil was vertically immersed in a mixed alkaline solution containing sodium hydroxide and (NH4)2S2O8, then rinsed with deionized water, and finally dried at a constant temperature of 25°C to obtain a Cu foil with a blue nanoscale Cu(OH)2 film on the surface; 4) Electrochemical in-situ synthesis of Cu / DNBT thin films The Cu foil coated with a blue nano-scale Cu(OH)2 film is immersed in a DNBT aqueous solution, the Cu foil coated with a blue nano-scale Cu(OH)2 film is used as an anode, and a platinum foil is used as an auxiliary electrode. After a coordination reaction, a light green film is obtained on the surface of the Cu foil, which is the Cu / DNBT film. Finally, the copper foil containing the Cu / DNBT film is taken out from the reaction solution, rinsed with deionized water, dried at 25° C. and then stored.
2. A method for preparing a Cu / DNBT@nano-Al energetic film, characterized in that: The steps include: 1) Dissolve nitrocellulose in acetone solution, then add Al powder and disperse under the action of ultrasound to obtain high-energy aluminum-containing ink; 2) Using a spin coating device, the high-energy aluminum-containing ink is uniformly coated on the surface of the Cu / DNBT film prepared by the method of claim 1; after the acetone evaporates, a dark green film is obtained on the surface of the Cu foil, which is the Cu / DNBT@nano-Al energetic film.
3. The method for preparing a Cu / DNBT thin film by electrochemical in-situ synthesis according to claim 1, characterized in that: In step 1), the amount of hydrochloric acid used is 60 mL, the amount of oxalic acid used is 20.0 g, and the amount of aminoguanidine bicarbonate used is 45.4 g.
4. The method for preparing a Cu / DNBT thin film by electrochemical in-situ synthesis according to claim 1, characterized in that: In step 2), in the sulfuric acid solution of DABT, the amount of DABT used is 11.9 g, and the amount of 20% sulfuric acid used is 140 mL; in the sodium nitrite aqueous solution, the amount of sodium nitrite used is 98.8 g, and the amount of water used is 40 mL; the concentration of sulfuric acid used for acidification is 20%.
5. The method for preparing a Cu / DNBT thin film by electrochemical in-situ synthesis according to claim 1, characterized in that: In step 3), the concentration of dilute sulfuric acid used for ultrasonic cleaning is 20%, and the ultrasonic cleaning time is 5 min; the concentration of sodium hydroxide in the mixed alkaline solution is 1.17 mol·L −1 , the concentration of (NH4)2S2O8 is 0.087 mol·L −1 , the immersion time of Cu foil in the mixed alkaline solution is 10 min.
6. The method for preparing a Cu / DNBT thin film by electrochemical in-situ synthesis according to claim 1, characterized in that: In step 4), the concentration of DNBT aqueous solution is 0.01 mol·L −1 , the dosage is 40 mL; the coordination reaction adopts a constant voltage of 1.5 V and the reaction time is 20 min.
7. The method for preparing the Cu / DNBT@nano-Al energetic film according to claim 2, characterized in that: In step 1), the amount of nitrocellulose used is 0.075 g, the amount of acetone used is 45 mL, the particle size of Al powder is 200 nm, the amount added is 0.425 g, and the ultrasonic dispersion time is 40 min.
Citation Information
Patent Citations
Preparation method of green insensitive nano-array initiating explosive
CN113862754A
High-energy low-sensitivity eutectic compound and preparation method thereof
CN117603150A